Politique Colonial D’enseignement Et Integration Scolaire Des Femmes Congolaises En Periode Coloniale Au Congo Kinshasa Exemple De Kisangani (Ex. Stanley Ville) - Olulu, Thérèse Olonga (European Scientific Journal, ESJ, 2017)
The setting up of a teaching layman system in view of the local (work hand) colonizer of the Congo Belge, constitute the way of entry of Kisangani (former stanley city) women in order to benefit the school formation, This, however, is in spite of the traditional reticence that was observed. As for what concerns the social consideration, this opportunity seems to have promoted the man more to the woman’s detriment. In fact, the documentary analysis and interview carried out with agents charged the archives of the primary and secondary education. Some women who were witness during the colonial time have helped in analysing this work. It comes out again that the minority which were considered to be the women of the city of Kisangani (former stanley city) was not neglected (disregarded). This means that some women were integrated into the school environment in the course of this period. However, in Kisangani, former Stanley city, girls’ schools which existed since 1924 such as Mapendano Secondary school and Grison primary school (domestic school) were created in 1935. Later in 1954, one of them gave attention to the creation of the primary girl’s schools amerced by the Mary missionary in the indigenous cities. However, these schools do not have an official objective to prepare the woman to participate in public life. This is because their objectives were not to prepare colonizer’s charging, but to offer him an auxiliary staff and maneuver (housewife, PP5 and D4 instructress). The bound factors of women experiences are not to be negligent based on their school integration. Nevertheless, this formation allowed auxiliary staff to widen their field of action to the public life involvement. This also is seen as a victory on the traditional brakes.